A Novel Controllable Hydrogen Sulfide-Releasing Molecule Protects Human Skin Keratinocytes Against Methylglyoxal-Induced Injury and Dysfunction - Chun-tao Yang; Yu Zhao; Ming Xian; Jian-hua Li; Qi Dong; Hong-bo Bai; Ji-de Xu; Mei-fen Zhang (Cellular Physiology and Biochemistry, 2014)
Background/Aim: Delayed wound healing is a common skin complication of diabetes, which is associated with keratinocyte injury and dysfunction. Levels of methylglyoxal (MGO), an α-dicarbonyl compound, are elevated in diabetic skin tissue and plasma, while levels of hydrogen sulfide (H2S), a critical gaseous signaling molecule, are reduced. Interestingly, the gas has shown dermal protection in our previous study. To date, there is no evidence demonstrating whether MGO affects keratinocyte viability and function or H2S donation abolishes these effects and improves MGO-related impairment of wound healing. The current study was conducted to examine the effects of MGO on the injury and function in human skin keratinocytes and then to evaluate the protective action of a novel H2S-releasing molecule. Methods: An N-mercapto-based H2S donor (NSHD)-1 was synthesized and its ability to release H2S was observed in cell medium and cells, respectively. HaCaT cells, a cell line of human skin keratinocyte, were exposed to MGO to establish an in vitro diabetic wound healing model. NSHD-1 was added to the cells before MGO exposure and the improvement of cell function was observed in respect of cellular viability, apoptosis, oxidative stress, mitochondrial membrane potential (MMP) and behavioral function. Results: Treatment with MGO decreased cell viability, induced cellular apoptosis, increased intracellular reactive oxygen species (ROS) content and depressed MMP in HaCaT cells. The treatment also damaged cell behavioral function, characterized by decreased cellular adhesion and migration. The synthesized H2S-releasing molecule, NSHD-1, was able to increase H2S levels in both cell medium and cells. Importantly, pretreatment with NSHD-1 inhibited MGO-induced decreases in cell viability and MMP, increases in apoptosis and ROS accumulation in HaCaT cells. The pretreatment was also able to improve adhesion and migration function. Conclusion: These results demonstrate that the novel synthesized H2S donor is able to protect human skin keratinocytes against MGO-induced injury and behavior dysfunction. We believe that more reasonable H2S-releasing molecules will bring relief to patients suffering from delayed wound healing in diabetes mellitus in the future.